Contrarians or momentum chasers? Individual investors' behavior when trading exchange‐traded funds. Issue 5 (28th November 2018) - Da Dalt, Carlo; Feldman, David; Garvey, Gerald; Westerholm, Peter Joakim
Abstract : Conducting the first study of momentum impact on households' exchange‐traded fund (ETF) trading behavior, we find that Finnish households are less contrarian when trading benchmark index ETFs than when trading common stocks. Also, their propensity to chase recent positive momentum is higher when purchasing ETFs than when purchasing stocks. As expected, results are stronger for ETF purchases than sales. Our findings are consistent with hypotheses that households are less overconfident trading index ETFs than common stocks, that contrarian behavior is more often rational when trading stocks than when trading ETFs, and that households trade ETFs for the long run.